Effects of Pancal G Powder on breeding results and temperament of farmed blue foxes (Alopex lagopus) - Niemelä, Paavo; Kerminen-Hakkio; Korhonen, Hannu T. (fi, 1997)
tutkimusraportti Daiichi Pharmaceutical Europe GmbH:lle 15.10.1997 V TUR